Regulation of chromatin interactions to the MYC oncogene by long non-coding RNA PVT1 in acute myeloid leukemia cell lines - Nur Zahwah Asa'ad Sameer Bagharib (2018)
Chromatin interactions have been found to play pivotal roles in important cellular events such as the regulation of gene expression, cell division and DNA replication. Dysregulated chromatin interactions can therefore have significant effects on the cell and promote diseases such as cancer. Chromatin interactions have been found to be regulated by long non-coding RNAs (lncRNAs) that act as enhancer RNAs. The establishment of chromatin interactions between PVT1 and MYC has been previously observed, suggesting a potential cis-regulatory role of lncRNA PVT1 in regulating MYC gene expression. Our study aims to investigate the regulation of lncRNA PVT1 in activating the MYC oncogene via chromatin interactions in Acute Myeloid Leukemia (AML) cell lines. Our hypothesis was tested by knocking down lncRNA PVT1 with siRNAs and studying PVT1 and MYC gene expression levels in AML cell lines. In this preliminary study, an efficient siRNA system was established as significant PVT1 knockdown was achieved. However, PVT1 knockdown did not reduce MYC transcript levels. As such, the cis-regulatory role of PVT1 in regulating MYC gene expression remains inconclusive, as more experiments such as Circular Chromosome Conformation Capture (4C) should be performed to study the effects of PVT1 knockdown on chromatin interactions of the MYC oncogene.